CHANGE MANAGEMENT OF SCHOOL ADMINISTRATORS AS PERCEIVED BY TEACHER UNDER SONGKHLA PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Kerdkhumthong, Witchayada; Taneerat, Boonlert (Journal of MCU Nakhondhat, 2024)
The aims of this study were to investigate change management of school administrators as perceived by teachers, to compare the change management of school administrators as perceived by teachers in relevance to their gender, educational level, academic standing, work experience, administrators’ gender and school size, and to examine problems with suggestions regarding change management of school administrators. This research study used two steps of proportional stratified random sampling and simple random sampling. The sample consisted of 297 teachers of the academic year 2022 under Songkhla Primary Educational Service Area Office 1. The data gathering instrument was a five-level rating scale questionnaire with the IOC ranged between 0.60 - 1.00 and the overall coefficient alpha of .987. The statistics used in the analysis comprised percentage, mean, standard deviation, One - way ANOVA, and Least Significant Difference (LSD). The results revealed that 1) The overall change management of school administrators as perceived by teachers was found at a good level. 2) Teachers with different work experiences, administrators’ academic standings, and school sizes, had significant differences in their perceptions at level of .001. Teachers with different genders had significant differences in their perceptions at level of .01, and no differences were found in other variables. And 3) Problems and suggestions indicated that some schools were short of personnel and fell short of budget. Some teachers and educational personnel refused to use technology. Therefore, administrators should reduce other workloads for teachers, develop their potentials, support and promote systematic use of technology in schools.